A covalent organic framework membrane with enhanced directional ion nanochannels for efficient hydroxide conduction. Issue 13 (7th March 2022) - Chen, Jia; Li, Ping; Zhang, Ningxin; Tang, Shaokun
Abstract : A covalent organic framework membrane with enhanced directional ion nanochannels for efficient hydroxide conduction. Abstract : The design and preparation of novel hydroxide-conducting materials for anion exchange membranes are urgently demanded for alkaline anion exchange membrane fuel cells (AEMFCs). Herein, we demonstrate a significantly enhanced hydroxide-conducting covalent organic framework (COF) membrane with effective directional hydroxide transport nanochannels. A novel COF named TJU-1 with intrinsic hydroxide conduction is synthesized by a bottom-up functionalization strategy for the first time, and then a COF membrane is fabricated via re-stacking of fibrous TJU-1. The quaternary ammonium groups at the end of the flexible side chains of TJU-1 can form continuous hydrophilic ionic domains within ordered channels of TJU-1, which makes rapid migration of hydroxide ions realizable. A remarkable hydroxide conductivity of 187 mS cm −1 (80 °C and 100% RH) and a maximum power density of 241 mW cm −2 are readily achieved. Particularly, the dimensional stability, mechanical properties, and swelling resistance of the TJU-1 COF membrane are dramatically promoted due to the rigid skeleton of the COF. Meanwhile, the interlayer interaction energy, micro-phase structure, and hydroxide ion transfer in TJU-1 are investigated by molecular dynamics simulations, which verify the important role of the ordered microchannel structure within TJU-1 in elevating hydroxide transport.